Experimental assessment of the productivity improvement when using U-shaped production cells with variable takt time. Issue 1 (2nd March 2015) - Pujo, Patrick; El Khabous, Ilham; Ounnar, Fouzia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aim of this research is to discuss the benefits of U-shaped layout for production cell operating in variable takt time. Different experiments were conducted using benchmarks to highlight the performance gap between a linear cell and a U-Cell. Design/methodology/approach – The implementation of the production cell, either in a U-shaped or in a straight line layout, is optimized through linear programming based on the number of operators. The two corresponding programs, in Mosel language, use the same approach to not introduce bias in the comparison of results. The study used the authors' own datasets and other well-known academic benchmarks. Findings – A comparison was conducted between the obtained takt times, with equivalent operating conditions, in both U-Cell and linear cell. A significant increase of the production rate was observed. This increase has often exceeded 10 per cent, reaching 32 per cent. All the experiments show that, with the same number of operators, a cell in a U-shaped layout is always at least as efficient, in terms of attainable production rates, than an equivalent linear cell. Ninety-six per cent of the studied cases give an improvement of production rate. Moreover, the dispersion of the U-Cell results is weaker, which suggests that the U-shaped layout gives better performances in more robust manner. Research limitations/implications – Results were obtained through a study of various academic benchmarks. The results must be validated on industrial situations. Practical implications – This paper will be very useful for researchers and practitioners to understand lean implementations and their derived benefits. This paper will allow them to evaluate and analyze the expected benefits of the implementation of the production cell in the U-shaped layout (operating in variable takt time). Originality/value – U-Cells constitute an appropriate solution for a layout of any kind of production cells with a variable structure (variability of the number of operators, of the organization of the cell, of the takt time […]). When facing a significant variation in the demand, the response consists of adjusting the number of operators assigned to the cell. This study jointly addresses the problem of the U-shaped layout and the operation in variable takt time.